Neurologic symptoms and diagnosis in adults with mast cell disease. - Smith, J; Butterfield, J; Pardanani, A; DeLuca, G; Cutrer, F (2011)
OBJECTIVE: To identify complications of mastocytosis that impact the nervous system across a large cohort. PATIENTS AND METHODS: In this retrospective series, we reviewed the electronic medical records of adult patients with a diagnosis of mastocytosis who were referred to a Neurologist at Mayo Clinic in Rochester, MN from January 1, 1999 to December 31, 2008. RESULTS: Thirty patients were identified who presented to a Neurologist with symptoms potentially related to the mast cell disease. Twelve of these patients presented with complex spells involving syncope, which frequently preceded a formal diagnosis of mastocytosis. Nine individuals presented with acute back pain which was ultimately deemed symptomatic of vertebral compression fractures. One individual experienced spinal cord compression from a vertebral mast cell infiltrate. Headaches were reported in 78/223 (35%) total patients with mastocytosis. Although details of headaches were insufficiently ascertained to diagnose most, the five individuals in our referral cohort met International Headache Society (IHS) criteria for migraine. Finally, three individuals (1.3%) were identified with multiple sclerosis occurring at variable times after the mast cell diagnosis. CONCLUSION: Symptoms related to mastocytosis may be encountered by neurologists and mimic many common, often idiopathic syndromes including, syncopal spells, back pain, and headache. In our cohort, multiple sclerosis may be over-represented. Mastocytosis should be considered in patients with these presentations, especially when also accompanied by flushing, abdominal cramping or diarrhea.